1999
DOI: 10.1021/jf980828t
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of Banana Starches

Abstract: Two varieties of banana green fruit growing in Guerrero, Mexico, were used for starch isolation. Chemical analysis and physicochemical and functional properties were studied in these starches. The "macho" variety presented higher starch yield than "criollo". In general, chemical compositions in both starches were similar, except in ash content, where the "criollo" variety showed a lower value than "macho". The results of freeze-thaw stability suggested that banana starches cannot be used in frozen products. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
2
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 13 publications
12
71
2
9
Order By: Relevance
“…Baker and Rayas-Duarte (1998) have reported this behavior for corn starches, mentioning low freeze-thaw gel stability for corn and amaranth starches. Likewise, Bello-Perez et al, (1999) found low gel stability in the same processes for banana starch. Low gel stability under these conditions suggests it is not convenient for use in food systems involving refrigeration or freezing processes.…”
Section: Freeze-thaw Stabilitymentioning
confidence: 87%
See 2 more Smart Citations
“…Baker and Rayas-Duarte (1998) have reported this behavior for corn starches, mentioning low freeze-thaw gel stability for corn and amaranth starches. Likewise, Bello-Perez et al, (1999) found low gel stability in the same processes for banana starch. Low gel stability under these conditions suggests it is not convenient for use in food systems involving refrigeration or freezing processes.…”
Section: Freeze-thaw Stabilitymentioning
confidence: 87%
“…Low water binding capacity of starches could be attributed to the involvement of a larger proportion of the hydroxyl groups in forming hydrogen and covalent bonds between the starch chains than with water (Hoover and Sosulski, 1986). Water chestnut starches has shown almost the same water binding capacity as macho and criollo banana starches (Bello-Perez et al, 1999). …”
Section: Water Binding Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…La claridad de las pastas de almidón se evaluó de acuerdo al método de Bello- Pérez et al (1999), determinando el porcentaje de transmitancia (%T) a 650 nm de pastas de almidón al 1% (p/p), previamente gelatinizadas y enfriadas a temperatura ambiente.…”
Section: Claridad De Las Pastasunclassified
“…Por otro lado, este rendimiento es mayor comparado con los reportados para otras fuentes no convencionales como el de almido´n de plá tano macho (Musa paradisiaca L., 438 g/kg) y chı´charo (Cicer arietinum L., 352 g/kg) (Bello- Pe´rez et al, 1999;Singh et al, 2004). En general, el rendimiento obtenido puede considerarse elevado compara´ndolo con el rendimiento de extraccio´n (675,8 g/kg) de almido´n de maı´z amarillo dentado obtenido por molienda hu´meda a nivel laboratorio, y el cual es una de las fuentes comerciales de almido´n (Aguilar y Eckhoff, 2007).…”
Section: Resultados Y Discusio´nunclassified